Optimal control of cable insulation cooling at extrusion line - Mitroshin, V. N.; Mitroshin, Y. V. (2016 2nd International Conference on Industrial Engineering, Applications and Manufacturing (ICIEAM), 2016)
The paper describes cooling polymer cable insulation covering a copper conductor at an extrusion line as a control object with distributed parameters. The issue of optimization of insulated wire cooling by water spatial temperature distribution in cooling baths with respect to the selected quality criterion was solved. The solution provides the desired approximation accuracy to the specified final insulation temperature distribution. The algorithms and technical solutions of significant energy consumption reduction and cooling baths length reduction are obtained. Proposed methodology of optimal design of water baths and cooling technological modes for cable products manufactured on extrusion lines ensures specified conditions of final products.